Origin of 1/f noise in graphene produced for large‐scale applications in electronics. Issue 1 (1st January 2015) - Kochat, Vidya; Sahoo, Anindita; Pal, Atindra Nath; Eashwer, Sneha; Ramalingam, Gopalakrishnan; Sampathkumar, Arjun; Tero, Ryugu; Viet Thu, Tran; Kaushal, Sanjeev; Okada, Hiroshi; Sandhu, Adarsh; Raghavan, Srinivasan; et al.
Abstract : The authors report a detailed investigation of the flicker noise (1/ f noise) in graphene films obtained from chemical vapour deposition (CVD) and chemical reduction of graphene oxide. The authors find that in the case of polycrystalline graphene films grown by CVD, the grain boundaries and other structural defects are the dominant source of noise by acting as charged trap centres resulting in huge increase in noise as compared with that of exfoliated graphene. A study of the kinetics of defects in hydrazine‐reduced graphene oxide (RGO) films as a function of the extent of reduction showed that for longer hydrazine treatment time strong localised crystal defects are introduced in RGO, whereas the RGO with shorter hydrazine treatment showed the presence of large number of mobile defects leading to higher noise amplitude.